Advantages and Disadvantages of Fiscal Discipline in Bulgaria in Times of Crisis - Vasil S. Petkov (Contemporary Economics)
The global economic crisis of 2008 has posed serious challenges to the Bulgarian economy and was reflected in worsened macroeconomic indicators. The subsequent sovereign debt crisis in Europe further aggravated the situation and blocked its path to recovery. In line with the overall sentiment in the European Union (the EU), Bulgaria made maintaining fiscal stability a priority that it set out to accomplish by following a policy of austerity. The country managed to achieve the desired effect relatively quickly. It became one of the best performers in terms of budget deficit and government debt as a share of GDP (which are among the lowest in the EU). These accomplishments underlie international institutions’ greater confidence in Bulgaria, which has led to an increase in its credit rating. Nevertheless, the state has not managed to reap the maximum benefits that this type of policy offers. Fiscal sustainability was accomplished at the expense of economic growth, the slow pace of which was accompanied by impoverishment of the population, high unemployment, restricted consumption, and operational difficulties faced by real-sector companies. These problems fueled doubts about the adequacy of strict budget discipline, especially in times of crisis. They provoked the author to examine in greater depth the benefits and the drawbacks that such a policy ultimately offers to Bulgaria. The results show that the strict fiscal measures have put additional pressure on the already fragile economic growth and have a high social cost as well. All this justifies the need for the government to take on a new course to achieve economic recovery by means of more active state support that would stimulate a pickup in consumption and production activity.